Profil Kondisi Fisik Atlet Futsal Satria Mandiri Kota Pasuruan - Rayes Maulana H.W; Moch Yunus; Yulingga Nanda Hanief (Politeknik Kampar, 2025)
This study aims to determine the profile of the physical condition of Satria Mandiri futsal athlete Pasuruan City. This research is a quantitative descriptive research. The subjects of this study were 30 Satria Mandiri futsal players in Pasuruan City. In this study, sampling used total sampling techniques. The data collection process was carried out using 4 instruments for each physical condition, namely: 1. Test the strength of the standing wide jump muscle 2. Sprint test (30-yard Sprint) 3. Agility test (Illinois agility run) 4. Aerobic endurance test (Bleep Test). Based on the results of physical condition tests on the Pasuruan City Satria Mandiri Team, it shows that the average leg muscle strength test results are 86.23